The Mental Health and Occupational Characteristic of Horse Stable Hand Workers in Korea - Kyung-Woo Kim; Sang-Gil Lee; Gyu-Seok Hwang (Elsevier, 2019)
The horse stable hand workers are one of the most important occupations in horse-racing industry. However, suicide problem of the horse stable hand workers in Korea has raised the necessity of new study on how these workers experience mental health problems such as occupational stress and depression in organizational situation. Therefore, this study investigated the occupational stress and depression level of the horse stable hand workers and identified the structural relationship in the horse-racing industry through a detailed interview. A total of 207 horse stable hand workers participated in this study, and occupational stress and depression level were surveyed using the Korean Occupational Stress Scale (KOSS) and Korean version of the Center for Epidemiologic Studies-Depression Scale (CES-D). The results of this study showed that the occupational stress level of horse stable hand workers was higher than the median of Korean population. The significant difference in occupational stress among the detail job grade was also identified. In addition, 34% of the horse stable hand workers showed high risk of depression, and job demand, organizational system, and inappropriate compensation as the subfactors of occupational stress were showed to mainly affect depression. Although there are some limitations according to the field survey, this study also has significant meaning in that it identifies the relationship between the occupational characteristics of the horse stable hand workers and the mental health. It will be necessary to study the diverse organizational situation and individual mental health for new occupations. Keywords: Depression, Horse stable hand worker, Mental health, Occupational stress